Functional characterisation of decoy receptor 3 in Crohn's disease. Issue 4 (27th November 2008) - Funke, B; Autschbach, F; Kim, S; Lasitschka, F; Strauch, U; Rogler, G; Gdynia, G; Li, L; Gretz, N; Macher-Goeppinger, S; Sido, B; Schirmacher, P; et al.
Abstract : Aims: Both epithelial barrier dysfunction and apoptosis resistance of immune cells contribute to the pathogenesis of Crohn's disease. The soluble decoy receptor 3 (DcR3) acts in an anti-apoptotic manner by neutralising the death ligand CD95L. Here, we investigated the possible involvement of DcR3 in Crohn's disease. Methods: The epithelial fraction of human small intestinal mucosa samples was obtained by laser microdissection. Expression of DcR3 was examined by global gene expression profiling, quantitative reverse transcription polymerase chain reaction, immunoblot analysis, and immunohistochemistry. DcR3 concentrations in the serum of patients with Crohn's disease were measured by enzyme-linked immunosorbent assay. Apoptosis assays were performed to study the effects of DcR3 in intestinal epithelial cells and lamina propria T cells. Results: DcR3 is over-expressed in the epithelial layer of ileum specimens in patients with Crohn's disease, both at actively inflamed and non-active sites. DcR3 serum levels are significantly elevated in patients with active and non-active Crohn's disease as compared to healthy controls. The expression of DcR3 in intestinal epithelial cells is induced by tumour necrosis factor α. Increased DcR3 expression is associated with activation of nuclear factor kappa B (NF-κB) and results in protection of intestinal epithelial cells and lamina propria T cells from CD95L-induced apoptosis. Conclusions: DcR3 may promote inflammation in Crohn's disease by inhibiting CD95L-induced apoptosis of epithelial and immune cells as well as by inducing NF-κB activation.